Control of common weeds in Wisconsin soybean cropping systems with pre‐emergence herbicides. Issue 1 (6th March 2022) - Ribeiro, Victor; Coura Oliveira, Maxwel; Smith, Daniel H.; Barbosa dos Santos, José; Werle, Rodrigo
Abstract: The integration of pre‐emergence (PRE) herbicides is an important component of sustainable long‐term weed management programs in soybean [ Glycine max (L.) Merr.]. The objective of this study was to evaluate the efficacy of 11 PRE herbicides on residual weed control in soybean. Field experiments were conducted in 2018 and 2019 at Arlington and Lancaster, WI. Herbicide treatments consisted of imazethapyr, chlorimuron‐ethyl, and cloransulam‐methyl (acetolactate synthase [ALS] inhibitors), metribuzin (photosystem II [PSII] inhibitor), sulfentrazone, flumioxazin, and saflufenacil (protoporphyrinogen oxidase [PPO] inhibitors), acetochlor, S ‐metolachlor, dimethenamid‐P, and pyroxasulfone (very long‐chain fatty acid [VLCFA] inhibitors), and a nontreated control. Predominant weed species included common lambsquarters, [ Chenopodium album (L.)], common purslane [ Portulaca oleracea (L.)], common ragweed [ Ambrosia artemisiifolia (L.)], giant foxtail ( Setaria faberi Herrm.), waterhemp [ Amaranthus tuberculatus (Moq.) J.D. Sauer], and yellow foxtail [ Setaria pumila (Poir.) Roem. & Schult.]. Visual weed control was assessed by species and weed biomass across species 65 days after treatment (DAT). The PRE herbicide efficacy varied across site‐years due to the different weed species present at each site. The ALS inhibitors controlled common purslane and common lambsquarters ≥95% 65 DAT at Arlington and Lancaster in 2018 but controlled waterhemp <50% at Lancaster in 2018 and 2019. The PPO inhibitors controlled waterhemp >90% 65 DAT at Lancaster in 2018 and 2019. The VLCFA inhibitors controlled common purslane, common lambsquarters, foxtail species, and waterhemp ≥70% 65 DAT across site‐years but ≤30% common ragweed control at Arlington in 2019. Results showcase the importance of knowing the weed species composition in the seedbank within each field; this can assist growers and crop advisers with selection of the appropriate effective PRE herbicide(s) that matches the weed species composition in each individual field. Core Ideas: Pre‐emergence (PRE) herbicide efficacy varied according to the weed community composition at each site‐year. PRE herbicides provided effective control of a wide range of weed species. PRE herbicides provide growers with additional sites of action for weed control in soybean. Effective PRE herbicides represent the foundation for chemical weed control in soybean.